2007
DOI: 10.1128/jb.01816-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics and Genomic Analysis of Scytonemin Biosynthesis in Nostoc punctiforme ATCC 29133

Abstract: The indole-alkaloid scytonemin is the most common and widespread sunscreen among cyanobacteria. Previous research has focused on its nature, distribution, ecology, physiology, and biochemistry, but its molecular genetics have not been explored. In this study, a scytonemin-deficient mutant of the cyanobacterium Nostoc punctiforme ATCC 29133 was obtained by random transposon insertion into open reading frame NpR1273. The absence of scytonemin under conditions of induction by UV irradiation was the single phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
125
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 40 publications
2
125
0
3
Order By: Relevance
“…Cells from 75 ml of a mid-exponential growth phase culture grown at 5°C, 30 ‰, and a photon flux of 12 µmol photons m -2 s -1 were pelleted by centrifugation, and pigments were extracted in 5 ml of ice-cold 100% acetone for 1 h. Cellular debris was removed by centrifugation, and the supernatant was filtered through a 0.22 µm polycarbonate filter, concentrated by evaporation on ice with a stream of N 2 gas, and stored at -40°C until analysis. The pigments in the extract were separated by HPLC by injecting 50 µl of the extract into a Spherisorb S10 ODS2 (10 mm by 250 mm) semi-prep analytical column filled with reverse-phase silica gel (Waters) and run on a variable solvent gradient of water, methanol, and acetone at a pressure of approximately 38 bar (Soule et al 2007). Pigments were detected continuously using an online photodiode array detector in the 405 to 665 nm range, identified by spectra, and quantified using published extinction coefficients (Köst 1988, Rowan 1989.…”
Section: Methodsmentioning
confidence: 99%
“…Cells from 75 ml of a mid-exponential growth phase culture grown at 5°C, 30 ‰, and a photon flux of 12 µmol photons m -2 s -1 were pelleted by centrifugation, and pigments were extracted in 5 ml of ice-cold 100% acetone for 1 h. Cellular debris was removed by centrifugation, and the supernatant was filtered through a 0.22 µm polycarbonate filter, concentrated by evaporation on ice with a stream of N 2 gas, and stored at -40°C until analysis. The pigments in the extract were separated by HPLC by injecting 50 µl of the extract into a Spherisorb S10 ODS2 (10 mm by 250 mm) semi-prep analytical column filled with reverse-phase silica gel (Waters) and run on a variable solvent gradient of water, methanol, and acetone at a pressure of approximately 38 bar (Soule et al 2007). Pigments were detected continuously using an online photodiode array detector in the 405 to 665 nm range, identified by spectra, and quantified using published extinction coefficients (Köst 1988, Rowan 1989.…”
Section: Methodsmentioning
confidence: 99%
“…The predicted structures of the gene products suggest that the assembly of scytonemin occurs in the periplasmic space (Soule at al., 2007). Scytonemin is synthesized in response to UV-A irradiation (Dillon et al, 2002;Fleming and Castenholz, 2007;Garcia-Pichel and Castenholz, 1991;Soule et al, 2007), consistent with the increase in the level of transcription of the scytonemin biosynthetic gene cluster (Sorrels et al, 2009;Soule et al, 2009). Moreover, scytonemin-producing cyanobacteria are typically found in the upper layers of microbial mat communities, which are exposed to high levels of solar irradiance (Balskus et al, 2011;Büdel et al, 1997).…”
mentioning
confidence: 99%
“…A gene cluster responsible for the production of scytonemin has been identifi ed in Nostoc punctiforme ATCC 29113 (Soule et al, 2007) and its biosynthetic pathway investigated to assign the functions of the gene products Walsh, 2008, 2009). The predicted structures of the gene products suggest that the assembly of scytonemin occurs in the periplasmic space (Soule at al., 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Nostoc punctiforme by Soule et al (2007) revealed that an 18-gene cluster (ORFs: NpR1276-NpR1259) is associated with scytonemin production and NpR1273 was directly involved in the biosynthesis process. Also four putative genes, NpR1271 to NpR1274, were found to be responsible for the assembly of the scytonemin molecule.…”
Section: Scytoneminmentioning
confidence: 99%